Respuesta :

Answer:

The solutions are (-√6,0) and (√6,0)

(-√5,-1) and (√5,-1)

Step-by-step explanation:

The equations are:

[tex] {x}^{2} + {y}^{2} = 6[/tex]

and

[tex] {x}^{2} - y = 6[/tex]

We make y the subject in the second equation to get;

[tex]y = {x}^{2} - 6[/tex]

We substitute into the first equation to get:

[tex] {x}^{2} + ({x}^{2} - 6 )^2= 6[/tex]

[tex]x = \pm \sqrt{6} [/tex]

and [tex]x = \pm \sqrt{5} [/tex]

The solutions are (-√6,0) and (√6,0)

(-√5,-1) and (√5,-1)

ACCESS MORE